2016
DOI: 10.5271/sjweh.3579
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and sickness absence: a systematic review and meta-analysis of the research literature

Abstract: Workplace bullying and sickness absence: a systematic review and meta-analysis of the research literature by Nielsen MB, Indregard AMR, Øverland S This review found that exposure to workplace bullying is a risk factor for later sickness absence. There is a shortage of studies on the moderators and mediators that can explain the relationship between bullying and absence. None of the identified studies examined if or how sickness absence increases the risk of later exposure to workplace bullying. Affiliation 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
114
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 54 publications
(89 reference statements)
12
114
1
3
Order By: Relevance
“…Miczek's clinical findings reinforce what Scandinavians (Eriksen, et al, 2014;Nielsen, et al 2016;Hoel, et al, 2010) who have been claiming, that workplace bullying truly is a health and safety issue. Targets of workplace bullying take more sick time, experience more apathy and depression as noted by targets' response to self-isolate from the organization and peers.…”
Section: Brain Damage and Bullyingsupporting
confidence: 74%
“…Miczek's clinical findings reinforce what Scandinavians (Eriksen, et al, 2014;Nielsen, et al 2016;Hoel, et al, 2010) who have been claiming, that workplace bullying truly is a health and safety issue. Targets of workplace bullying take more sick time, experience more apathy and depression as noted by targets' response to self-isolate from the organization and peers.…”
Section: Brain Damage and Bullyingsupporting
confidence: 74%
“…This claim has since been reiterated by other scholars (e.g. Lutgen-Sandvik, 2003;Strandmark & Hallberg, 2007), and researchers have repeatedly reported outcomes of bullying related to expulsion, including sickness absence (Niedhammer, Chastang, Sultan-Taïeb, Vermeylen, & Parent-Thirion, 2013;Nielsen, Indregard, & Øverland, 2016), increased turnover rates (Hogh, Hoel, & Carneiro, 2011;Quine, 2001) and unemployment (Glambek et al, 2015). Furthermore, research has demonstrated severe health effects of workplace bullying .…”
Section: Workplace Bullying As An Antecedent Of Job Insecuritymentioning
confidence: 86%
“…Although bullying has been found to increase the risk of subsequent health problems 7–9 and sickness absence, 10 the empirical evidence for bullying as a precursor to disability retirement is scarce and findings are somewhat mixed with some studies supporting bullying as a precursor, 5,1113 whereas others provide ambiguous findings. 14 In addition, there is lack of evidence on the relative impact of bullying given the influence of other work exposures and the impact of gender on the association has not been established.…”
mentioning
confidence: 99%